Multisensory stimulation and its effect on breast milk volume production in mothers of premature infants - Cuya, Carla Madeleine; Barriga, Carlos; Graf, Maria del Carmen; Cardeña, Mirta; Borja, María del Pilar; Condori, Richard; Azocar, Moises; Cuya, Carlos (Frontiers in Pediatrics, 2024)
Introduction: In a significant number of NICUs, mothers are unable to provide enough maternal milk to feed their premature babies, so healthcare workers rely on human milk banks. Unfortunately, this service is not available in many countries, such as Peru, where premature infants receive formula. The aim of this study was to determine the effectiveness of multisensory stimulation on mother´s own milk production. Methods: Participants in this study were postpartum mothers of preterm infants 27 to 37 weeks gestational age. The participants were assigned to three groups: 1) audiovisual stimulation (SAV) (n = 17), 2) audiovisual and olfactory stimulation (SAVO) (n = 17), and 3) control (n = 16). A questionnaire was used to collect demographic and obstetric data, including a record of mother´s own milk volume. Results: There was no significant difference between the SAV, SAVO and control groups regarding age, marital status, education level, occupation, number of children, mode of delivery, Apgar and birth weight. On the other hand, a significant difference was observed between the SAV and SAVO groups regarding the amount of milk produced, with higher production between the fourth and seventh day (Tukey p <0.05). Similarly, milk volume was significantly greater in the SAVO group compared to the SAV and control groups (OR=1.032, 9/5% CI=1.0036-1.062, p 0.027). Conclusion: Multisensory stimulation in postpartum mothers of preterm infants caused an increase in the volume of mother´s own milk production. However, more research is needed to explain the findings presented in this study.